Digital transformation in the global automotive industry. (25th November 2021) - Sommer, Stefan; Proff, Heike; Proff, Harald
In the automotive industry, digitalisation is causing discontinuous and thus often disruptive changes that are driving changes in companies' traditional processes, products/services and business models. However, research has not yet adequately examined the extent of the digital transformation in the automotive industry and options for accelerating it. In this study, an index of digital maturity is theoretically deduced to measure digitalisation in order to examine 167 global automotive companies. The results indicate that digital transformation is primarily a strategic transformation. However, it frequently fails to make proper progress because larger companies have complex structures, often assembled through cooperative ventures and acquisitions, and organisational units test isolated, mostly unconnected pilot applications of digital technologies in processes, products/services and business models at many points in the organisation. Therefore, responding to digital disruption in the automotive industry is a comprehensive transformational task.